FABRICATION OF 2-5 µM HYGROSCOPIC SEEDING MATERIAL FOR RAIN ENHANCEMENT PURPOSES - Dini Harsanti; Krisna Adhitya; Safrizal Safrizal (Jurnal Sains & Teknologi Modifikasi Cuaca, 2021)
Abstract Hygroscopic cloud seeding, which uses giant cloud condensation nuclei (GCCN) particles with diameters between 2-5 µm, has been known to be 100 times more effective compared to those that use hygroscopic flares. Micronisation through jet milling has been recognized as the most common and ubiquitous method used to obtain particles with such a narrow size (2-5 µm) distribution. This research has successfully developed and identified 2-5 µm NaCl powders mixed with 10% cab-o-sil anticaking agent and 2 (two) times jet milling frequency as a potential GCCN (hygroscopic) seeding material. We use a combination of jet mill micronisation, rough milling with a Cross-Beather Mill, and analytical sieving to produce powders with those mentioned above (2-5 µm) size distribution. We varied the anticaking agent percentage in the mixture and the jet milling process frequency to identify which parameters would result in the 2-5 µm size distribution. We then confirmed the micronisation results particle size distribution with a particle size analyzer (PSA) and its morphology with a scanning electron microscope (SEM) machine. The materials with the 10% cab-o-sil agent mixture were confirmed to have the aforementioned size distribution from the characterization results. Intisari Penyemaian awan higroskopis menggunakan partikel giant cloud condensation nuclei (GCCN) dengan diameter 2-5 m telah diketahui 100 kali lebih efektif dibandingkan dengan yang menggunakan flare higroskopis. Mikronisasi melalui jet milling telah dikenal sebagai metode yang paling umum dan banyak digunakan untuk mendapatkan partikel dengan distribusi ukuran sempit (2-5 µm). Penelitian ini berhasil mengembangkan dan mengidentifikasi serbuk NaCl 2-5 µm yang dicampur dengan 10% anti gumpal berupa Cab-O-Sil dan frekuensi jet milling 2 (dua) kali sebagai bahan penyemaian GCCN (higroskopis) potensial. Pada penelitian ini telah digunakan kombinasi mikronisasi jet mill, penggilingan kasar dengan Cross-Beather Mill, dan ayakan analitik untuk menghasilkan serbuk dengan distribusi ukuran yang disebutkan di atas (2-5 µm). Telah divariasikan pula persentase bahan anti gumpal dalam campuran dan frekuensi proses jet milling untuk mengidentifikasi parameter yang akan menghasilkan distribusi ukuran 2-5 µm. Distribusi ukuran partikel hasil mikronisasi tersebut kemudian dikonfirmasi dengan alat analisa ukuran partikel (PSA) dan morfologinya dengan mesin scanning electron microscope (SEM). Dari hasil karakterisasi, material dengan campuran anti gumpal Cab-O-Sil sebanyak 10% dipastikan memiliki sebaran ukuran tersebut.